How Balanced Is Multilingualism in Scholarly Journals? A Global Analysis Using the Directory of Open Access Journals (DOAJ) Database - Gimena del Rio Riande; Ivonne Lujano Vilchis (Journal of Electronic Publishing)
The concept of balanced multilingualism aims to establish “instruments for documenting and measuring the use of language for all the different purposes in research, thereby providing the basis for the monitoring of further globalization of research in a more responsible direction” (Sivertsen, 2018, p. 2). However, an analysis of the Directory of Open Access Journals (DOAJ), the largest database of fully open access journals produced in 130 countries, does not show balanced multilingualism in the global landscape. The DOAJ promotes linguistic diversity by indexing journals in 80 languages, including dialectal variations, indigenous languages, and languages spoken by less than 50,000 speakers (eg, Aragonese). In this article, we present the main trends related to the languages in which journals publish their full-text contributions to respond to this unbalanced landscape. We conducted a descriptive analysis of the 17,564 journals listed in the DOAJ (July 2023). Our findings show that 65% (11,331) of the journals listed publish only in one language, and 35% (6,234) publish in two, three, and up to 16 languages. Our research also shows that 50% of the multilingual journals are based in Asia, Southern and Eastern Europe, and Latin America.